O-B06 The Impact of Covid-19 on Bariatric surgery in England during 2020. (16th December 2021) - Sandland-Taylor, Laura; Jenkins, Barbara; Beckingham, Ian
Abstract: Background: The Covid-19 pandemic had a significant impact on NHS services across England. Due to the significant rise in demand for beds in both ward and ITU environments, trusts were forced to reduce the number of operations carried out to help reduced the burden on secondary care services. Whilst efforts were made to preserve operations where possible, the Covid-19 burden has had a significant impact on bariatric surgery throughout 2020. The following research looks at the true impact of Covid-19 on bariatric surgery in England and analyses this in relation to the Covid-19 burden. Methods: Data relating to operation numbers was taken from The Surgical Workload Outcomes Audit (SWORD) database. The SWORD database was interrogated for the years 2017 – 2020. A mean number of operations was calculated using the 2017-2019 data and compared to data from 2020 for gastric bypass, sleeve gastrectomy, gastric banding and biliopancreatic diversion. Operations performed and other demographic data was analysed regionally and compared to Covid-19 deaths throughout England. Covid-19 data was obtained from the national government dashboards. Results: The results of the study show that Nationally there was a significant decline in bariatric surgery operations carried out throughout 2020 due to the Covid-19 pandemic. Overall there was a 53.5% reduction in bariatric surgery operations carried out in 2020. Looking at the individual operation types, there was a 50.7% reduction in gastric bypass surgery, a 50% reduction in biliopancreatic diversion and a 51.9% reduction in sleeve gastrectomy. There was a greater reduction in gastric bands, with a 78.1 % reduction in procedures which may also reflect changes in current practice with regards to the use of gastric bands. On reviewing data at a local level, all trusts were significantly impacted by the pandemic with the reduction in services ranging from 50% to 100% reduction in operations performed. Conclusions: Overall, despite national efforts to preserve as many operations as possible, there was a significant reduction in the delivery of bariatric surgery services throughout England during the Covid-19 pandemic. Due to this reduction in service provision, it is likely that there are now much larger waiting lists which will need to be addressed as we recover from the Covid-19 pandemic. Whilst there was a similar reduction in services across most trusts due to the elective nature of the operations, variation should be further analysed to allow for better planning and resource allocation for futor future waves or future pandemics.